Ameliorating effect of guava (Psidium guajava) extract on adriamycin induced reproductive toxicities (2015)
This study was undertaken to investigate the protective effects of guava extract on Adriamycin induced reproductive toxicities. For this purpose, thirty adult male Wistar rats were randomly divided into 6 treatment groups. Group 1, the control, was administered distilled water while group 2 was treated with Adriamycin (ADR)(30 mg.m–2) alone. Groups 3, 4 and 5 were administered combinations of 30 mg.m–2 (ADR) and graded doses (125 mg.kg–1; 250 mg.kg–1; 500 mg.kg–1, respectively) of guava extract. Group 6 was treated with the extract (500 mg.kg–1) alone. The treatments were done for seven days with water and feed provided ad libitum. The effects of these treatments on the reproductive characteristics of the male Wistar rats were thereafter investigated. The results showed that the control group (1) had a significantly higher sperm count (96.25 ± 3.84 × 106 cells.ml–1) and motility (80.00 ± 4.08 %) compared to the other treatment groups (P < 0.05). Group 3 had a significantly lower sperm count (40.00 ± 0.00 × 106 cells.ml–1) compared with the group 4 (67.33 ± 4.81 × 106 cells.ml–1) and 6 (62.60 ± 3.09 × 106 cells.ml–1). Group 5 had the lowest percentage livability (50 %), which was significant when compared with the control group, but not significant compared with the other treatment groups (P < 0.05). Groups 3, 5 and 6 had over 20 % sperm cell abnormalities. Most prominent of the abnormalities in groups 3 and 5 were curved tails and curved mid pieces in group 6. This work showed that guava extract at 250 mg.kg–1 is safe and gave protective cover to ADR induced reproductive toxicities.